2013
DOI: 10.1111/infa.12013
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence and Stability of the Attentional Bias to Fearful Faces in Infancy

Abstract: Several studies have shown that at 7 months of age, infants display an attentional bias toward fearful facial expressions. In this study, we analyzed visual attention and heart rate data from a cross‐sectional study with 5‐, 7‐, 9‐, and 11‐month‐old infants (Experiment 1) and visual attention from a longitudinal study with 5‐ and 7‐month‐old infants (Experiment 2) to examine the emergence and stability of the attentional bias to fearful facial expressions. In both experiments, the attentional bias to fearful f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
113
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(130 citation statements)
references
References 48 publications
13
113
3
Order By: Relevance
“…This increased attention to fear in others is in line with prior behavioral and neuroscience work with infants of that age (3,(62)(63)(64)(65)69). Enhanced attention to fear has been argued to serve important adaptive functions because it is thought to alert the individual to potential dangers and threats in the environment (69). Interestingly, although fearful and angry faces both represent negative expressions that might be associated with threat, our results show that infants dedicate more attention to fearful eyes than angry eyes.…”
Section: Discussionsupporting
confidence: 88%
“…This increased attention to fear in others is in line with prior behavioral and neuroscience work with infants of that age (3,(62)(63)(64)(65)69). Enhanced attention to fear has been argued to serve important adaptive functions because it is thought to alert the individual to potential dangers and threats in the environment (69). Interestingly, although fearful and angry faces both represent negative expressions that might be associated with threat, our results show that infants dedicate more attention to fearful eyes than angry eyes.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to the current findings, it is important to mention that infants' sensitivity to emotional facial expressions is in place by 7 months of age. Specifically, 7-month-old infants, but not 5-month-old infants, have been shown to discriminate between different emotional facial expressions and show an attentional bias for fearful facial expressions (Jessen & Grossmann, 2016;Peltola, Hietanen, Forssman, & Leppänen, 2013;Peltola et al, 2009). These studies show that this fear bias can be observed in infants' looking time and in their ERP responses.…”
Section: Discussionmentioning
confidence: 70%
“…These studies show that this fear bias can be observed in infants' looking time and in their ERP responses. More specifically, 7-month-old infants look longer at fearful compared with happy faces (Peltola et al, 2009) and are slower to disengage attention from fearful faces compared with happy faces or nonemotional novel facial expressions (Peltola et al, 2013;Peltola, Leppanen, Palokangas, & Hietanen, 2008). At the neural level, the Nc has been shown to distinguish between positive (happy) and negative (fearful) facial expressions with a larger amplitude to fear, indexing a greater allocation of attention ( Jessen & Grossmann, 2015;Peltola et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not until the age of 7 mo that they show a robust attentional bias to fear, as reflected in their neural and behavioral responses (37)(38)(39)(40)(41). The developmental emergence of this fear bias has been linked to the maturation of frontolimbic circuits (42)(43)(44)(45) and occurs at a point in development when infants begin to first experience fear themselves (46,47).…”
Section: Significancementioning
confidence: 99%